The Influence of Marketing Mix on Consumer Purchasing Decisions at Nita Mandiri Clothing Store, Ambon City - Nudin, Randi; Rehatta, Geradin; Louhenapessy, William George M (JENDELA PENGETAHUAN, 2025)
This study aims to analyze the effect of the marketing mix (product, price, promotion, and place) on consumer purchasing decisions at Nita Mandiri Clothing Store in Ambon City. This research uses a quantitative approach with the Simple Random Sampling technique, involving 97 respondents. Data were collected through questionnaires designed on a Likert scale and analyzed using SPSS 25 for validity, reliability, multiple linear regression, as well as t-test and F-test. The results show that price and place variables have a positive and significant effect on purchasing decisions, while product and promotion variables do not have a significant effect. Simultaneously, the four independent variables (product, price, promotion, and place) significantly influence consumer purchasing decisions. Therefore, optimizing competitive pricing strategies and strategic locations is essential to enhance purchasing decisions at Nita Mandiri Clothing Store. This study provides recommendations for store owners to improve promotion strategies and product innovation to attract more consumers